Razlozi zasnovani na efikasnosti za obaveštenje o docnji i anticipirano dospeće u rumunskom građanskom pravu - Ungureanu, Iulia Georgiana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
This study examines the rational bases based on the efficiency criterion regarding the default and anticipated maturity in Romanian civil law, with particular reference to Articles 1417, 1418, 1522 and 1523. of the Civil Code. The analysis emphasizes the dual function of the debtor's default: preserving the contractual balance through a rebuttable presumption of tolerance, on the one hand, and protecting the interests of creditors by providing timely access to remedies, on the other. A reminder of late payment functions as an economically efficient mechanism, striking a balance between the principle of favor contractus and the creditor's right to compensation, while a delay by force of law accelerates access to remedies through absolute presumptions that preclude toleration of delay. The central question relates to the interplay between the loss of benefit from the term and the debtor's default: whether the anticipated maturity can be caused by situations of late payment and, conversely, whether the loss of benefit from the term can automatically imply a delay.
Keywords: neizvršenje obaveze dužnika; pretpostavka (oboriva/neoboriva); očekivano dospeće; gubitak koristi od roka; ugovorna sredstva zaštit